2009
DOI: 10.1002/ejic.200801121
|View full text |Cite
|
Sign up to set email alerts
|

O‐Acylated 2‐Phosphanylphenol Derivatives – Useful Ligands in the Nickel‐Catalyzed Polymerization of Ethylene

Abstract: The title ligands were prepared by O-acylation of 2-diphenylphosphanyl-4-methylphenol (1) or directly by double lithiation of 2-bromo-4-methylphenol and stepwise coupling with ClPPh 2 and ClP(O)Ph 2 or RC(O)Cl (R = Me, tBu, Ph, 4-MeOC 6 H 4 ) to afford diphenylphosphinate 2 and carboxylic esters 3a-d. X-ray crystal structure analyses of 3b-d show conformations in which the P-phenyl substituents are rotated away from the ester group and the C(O)O π planes are nearly perpendicular to the phenol ring π plane. O-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Since no colloidal nickel was observed, formation of an inactive complex is assumed. It was earlier observed that ethanol is unsuitable as solvent in the PPHH/Ni -catalyzed ethylene polymerization and that it promotes the formation of catalytically inactive nickel bis(phosphinophenolates) . It is assumed that a slow but in principle similar complex formation is induced by the OH group of the comonomer which competes with the polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since no colloidal nickel was observed, formation of an inactive complex is assumed. It was earlier observed that ethanol is unsuitable as solvent in the PPHH/Ni -catalyzed ethylene polymerization and that it promotes the formation of catalytically inactive nickel bis(phosphinophenolates) . It is assumed that a slow but in principle similar complex formation is induced by the OH group of the comonomer which competes with the polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…During our studies on tuning of 2-phosphinophenolate nickel catalysts for oligo- or polymerization of ethylene, we observed improved catalyst stability and ethylene conversion if olefins were added . A closer study showed slight to substantial incorporation of linear α-olefins if these were added as comonomers.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation